Optical quality tetragonal phase single-crystal fiber of potassium di-hydrogen phosphate with efficient second-harmonic generation. Issue 5 (14th December 2016) - Ren, Yan; Zhang, Shao Jun
Abstract : Flexible single-crystal potassium di-hydrogen phosphate fibers with efficient second-harmonic generation open great potential of this crystal in micro-optic applications. Abstract : Optical quality tetragonal phase quasi one-dimensional single-crystalline fibers of potassium di-hydrogen phosphate with a large length-to-diameter ratio and high flexibility have been grown. Efficient guided-wave optical second harmonic generation is achieved along the growth axis. The single-crystal fibers open great potential of potassium di-hydrogen phosphate crystals in micro-photonic applications.